Effects of aging on the electrical resistivity of La1-xBxCoO3 perovskites (B = Sr, Ca, Ba; 0.20 ≤ x ≤ 0.30) - Mira, J. (2000)
A study of the reliability of the title compounds as a basis for magnetoresistive sensors is presented. For this purpose we have carried out long-term systematic studies of the evolution of the resistive and magnetic properties of samples synthesized by both ceramic and wet chemical routes, allowing them to age during several months. It is observed that, although the magnetic properties remain unaltered, their resistivity does change appreciably. With time, samples that are initially metallic over all the measured temperature range (T < 300 K), change to semiconductor-like behaviour at low temperatures and above their ferromagnetic to paramagnetic phase transition temperature, giving rise to a 'reentrant semiconducting behaviour' with associated high electrical noise, relaxation effects of the resistivity and even diodic behaviour.